Pemberdayaan Masyarakat Desa Melalui Sosialisasi Aquaponik Guna Mendukung Ketahanan Pangan Di Desa Bukit Kratai Kecamatan Rumbio Jaya Kabupaten Kampar - Alpata Hilla; Ledy Diana; Aulia Fadhilah; Bintang Surya; Daniella Sri Rani Purba; Dimas Ariasandi; Faira Aisyah; Jhon Pinter Agustinus Bulolo; Nadia Afta; Putri Tasya; Rika Putri Patricia; Ryan Hidayat (Unri Conference Series: Community Engagement, 2025)
Community service activities carried out in Bukit Kratai Village, Kampar Regency, aim to increase community knowledge and skills in utilizing the aquaponics system as an effort to support family food security. Aquaponics is an integrated farming technique that combines growing vegetables and fish in one mutually supporting system without soil. The Family Welfare Development Group (PKK) and the Women's Farmers Group (KWT) are involved in implementing a participatory approach through outreach, training and workshops. The materials and tools used come from used goods such as plastic bottles, jerry cans and styrofoam, so they are easy to use and cheap. The results show that people understand more about the importance of implementing an aquaponics system at home. The community is motivated to develop this system as an environmentally friendly source of food and additional income. Ultimately, this program has the potential to strengthen food security and empower communities through the application of simple, environmentally based technology.